KEPUTUSAN PEMBELIAN JERSEY ORISINAL PERSEBAYA MUSIM 2024/2025: PENGARUH FANATISME DAN DESAIN PRODUK - Anang Rizqi Saputra; Zumrotul Fitriyah (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Persebaya is one of the clubs wih the largest fanatical supporter base in Indonesia. Fanatical fans tend to have strong emotional ties and purchase their favorite products, with unique and superior product designs being an important factor in attracting consumers. However, imitation jerseys are still widely sold an in high demand. This study aims to examine the influence of fanaticism and product design on the decision to purchase original Persebaya jerseys for the 2024/2025 season in Surabaya. The study population consists of Persebaya jersey consumers residing in the city of Surabaya. The sample size comprises 99 respondents. The research method employs a quantitative approach. Sample criteria include consumers who have purchased original Persebaya jerseys for the 2024/2025 season, Persebaya fans, and individuals aged 17 years or older. Data was collected through a google forms questionnaire and analyzed using structural equation modeling with the assistance of the SmartPLS 3.0 apps. The results of the analysis indicate that fanaticism and product design have a positive influence on the decision to purchase the original Persebaya jersey for the 2024/2025 season.